2022
DOI: 10.3390/cancers14174299
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Activity of Cannabis sativa Phytocannabinoids: Molecular Mechanisms and Potential in the Fight against Ovarian Cancer and Stem Cells

Abstract: Ovarian cancer (OC) is the most lethal gynecological malignancy, with about 70% of cases diagnosed only at an advanced stage. Cannabis sativa, which produces more than 150 phytocannabinoids, is used worldwide to alleviate numerous symptoms associated with various medical conditions. Recently, studies across a range of cancer types have demonstrated that the phytocannabinoids Δ9-trans-tetrahydrocannabinol (THC) and cannabidiol (CBD) have anti-cancer activity in vitro and in vivo, but also the potential to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 89 publications
(192 reference statements)
1
3
0
Order By: Relevance
“…The obtained results confirmed the remarkable anticancer activity of the C. Sativa extracts against different carcinoma cell lines (AGS, A375 and A549). This agreed well with previous works that studied the anticancer activity of C. sativa on different cell lines such as melanoma [20], ovarian cancer [21], prostate cancer [22], and breast and pancreatic cancer [16], among others. The results are also in agreement with the biological activities based on both the chemotype and the extraction taken from the leaves of the plant.…”
Section: Cytotoxicity and Anticancer Activity Of C Sativa Leaf Extractssupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results confirmed the remarkable anticancer activity of the C. Sativa extracts against different carcinoma cell lines (AGS, A375 and A549). This agreed well with previous works that studied the anticancer activity of C. sativa on different cell lines such as melanoma [20], ovarian cancer [21], prostate cancer [22], and breast and pancreatic cancer [16], among others. The results are also in agreement with the biological activities based on both the chemotype and the extraction taken from the leaves of the plant.…”
Section: Cytotoxicity and Anticancer Activity Of C Sativa Leaf Extractssupporting
confidence: 92%
“…It is established that C. sativa chemotypes’ rich cannabinoid and terpenoid content offer better pharmacological activities that are able to broaden clinical applications and improve therapeutic issues [ 17 , 18 , 19 ]. In the same way, remarkable anticancerogenic activity has been demonstrated for C. sativa extracts against different carcinoma cell lines such as melanoma [ 20 ], ovarian [ 21 ], prostate [ 22 ], breast [ 23 ], and pancreatic cancer [ 16 ]. These studies have revealed a reduction in tumor growth and promotion of apoptosis and autophagy in carcinoma cells [ 15 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial that the accurate separation and recognition of malignant tissues be programed and designed, which entails understanding mechanisms that regulate the expansion of cancer stem cell colonies and the development of drug resistance in order to design effective tailored therapies. The immunomodulation, immune evasion, and impact resistance brought about by CSCs significantly alter the ability of the natural immune system to work in harmony [ 116 , 117 ]. In tumor progression, signaling via mTOR (mammalian target of rapamycin), SHH (sonic hedgehog), notch receptor, and Wnt/ β -catenin can be harnessed for modulating tumor progression [ 118 ].…”
Section: Treatment and Side Effects Associated With Stem Cell Therapymentioning
confidence: 99%
“…Phytocannabinoids have been found to affect cancer cells and tumors via several different genetic pathways and molecular mechanisms. For example, several signal transduction pathways can be activated by phytocannabinoids to induce cancer cell death, including cell cycle arrest, endoplasmic reticulum (ER) stress, oxidative stress, autophagy and/or apoptosis ( Hinz and Ramer, 2019 ; Kovalchuk and Kovalchuk, 2020 ; Tomko et al, 2020 ; Koltai and Shalev, 2022 ).…”
Section: Introductionmentioning
confidence: 99%